Pelaksanaan Koordinasi Badan Perencanaan Pembangunan Daerah Provinsi Riau Dalam Penyusunan Rencana Kerja Pemerintah Daerah 2023 - Manda Rafika; Dita Fisdian Adni (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
Coordination between regional government agencies plays a crucial role in the preparation of the Regional Government Work Plan (RKPD) to ensure that planned programs and activities align with regional development priorities. This study aims to analyze the implementation of coordination by the Riau Province Regional Development Planning Agency (Bappeda) in the preparation of the 2023 Regional Government Work Plan and to identify obstacles encountered during the process. This study employed a qualitative method with a descriptive approach. Data were obtained through observation, interviews, and documentation of informants directly involved in the preparation of the 2023 RKPD at the Riau Province Regional Development Planning Agency and the Riau Province Public Works and Spatial Planning Office. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The study shows that the Implementation of the Coordination of the Riau Province Regional Development Planning Agency on communication indicators has been running well through coordination meetings, discussion forums, official letters and online communication media, the implementation of coordination on the integration indicator has been running well through joint discussions, division of tasks according to functions and adjustment of activity programs with regional development priorities and the implementation of coordination on the synchronization indicator has been carried out well, synchronization is carried out through the process of verifying program proposals, adjustments to the RKPD, Renstra and Renja of regional devices. Obstacles faced in the Implementation of the Coordination of the Riau Province Regional Development Planning Agency in the Preparation of the 2023 Regional Government Work Plan include the replacement of representatives of regional apparatus organizations, suboptimal cross-sector coordination, delays in the issuance of General Guidelines for the preparation of the RKPD, delays in submitting supporting data and coordination adjustments due to the implementation of the Work From Home (WFH) system.